A propensity score–matched analysis indicates screening for asymptomatic coronary artery disease does not predict cardiac events in kidney transplant recipients - Forsythe, John; Nimmo, Ailish; Oniscu, Gabriel; Robb, Matthew; Watson, Christopher; Fotheringham, James; Roderick, Paul; Ravanan, Rommel; Taylor, Dominic (Elsevier, 2021)
Screening for asymptomatic coronary artery disease prior to kidney transplantation aims to reduce peri- and postoperative cardiac events. It is uncertain if this is achieved. We investigated whether pre-transplant screening with a stress test or coronary angiogram associates with any difference in major adverse cardiac events (MACE) up to 5 years post-transplantation. We examined a national prospective cohort recruited to the Access to Transplant and Transplant Outcome Measures study who received a kidney transplant between 2011-2017, and linked patient demographics and details of cardiac screening investigations to outcome data extracted from the Hospital Episode Statistics dataset and UK Renal Registry. Propensity score matched groups were analysed using Kaplan-Meier and Cox survival analyses. Overall, 2572 individuals were transplanted in 18 centres; 51% underwent screening. The proportion undergoing screening by centre ranged from 5-100%. The incidence of MACE at 90 days, 1 and 5 years was 0.9%, 2.1% and 9.4% respectively. After propensity score matching based on the presence or absence of screening, 1760 individuals were examined (880 in screened and unscreened groups). There was no statistically significant association between screening and MACE at 90 days (hazard ratio [HR] 0.80, 95% CI 0.31-2.05), 1 year (HR 1.12, 95% CI 0.51–2.47) or 5 years (HR 1.31, 95% CI 0.86-1.99). Age, male sex and history of ischaemic heart disease were associated with MACE. There is no association between screening for asymptomatic coronary artery disease and MACE up to 5 years post-transplant. Practices involving unselected screening of transplant recipients should be reviewed
Keywords: cardiovascular events; coronary artery disease; kidney transplantation; screening; Coronary Artery Disease; Humans; Kidney Transplantation; Male; Propensity Score; Prospective Studies; Retrospective Studies; Risk Factors; Transplant Recipients; United Kingdom